2012
DOI: 10.1007/s00330-012-2413-6
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal fat distribution on computed tomography predicts ureteric calculus fragmentation by shock wave lithotripsy

Abstract: • Unenhanced CT is now widely used to assess ureteric calculi. • The same CT protocol can provide measurements of abdominal fat distribution. • Ureteric calculi are usually treated by shock wave lithotripsy (SWL). • Greater intra-abdominal fat stores are generally associated with poorer SWL results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Juan et al showed the impact of SSD on the obtained results of ESWL while SSD more than 10 cm is likely led to treatment failure. Their results are also consistent with our finding (15).…”
Section: Discussionsupporting
confidence: 94%
“…Juan et al showed the impact of SSD on the obtained results of ESWL while SSD more than 10 cm is likely led to treatment failure. Their results are also consistent with our finding (15).…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have shown that NCCT provides a rapid assessment of the stone size, stone surface area, HU density, SSD, stone number, and stone location, and all these parameters have attempted to predict the successful rate of SWL [13,17]. Recently, several investigators have demonstrated that BMI, AD CT , and intra‐abdominal fat distribution can also help to predict the outcome of SWL [10,18–20]. In the present study, we tried to combine these potential parameters, which were available by NCCT, to predict the outcome after shockwave lithotripsy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a report from Pareek et al [ 3 ] that SSD is related to successful SWL, its role has remained controversial. While some studies have confirmed that SSD is an important factor in predicting treatment outcomes [ 2 , 5 , 8 , 10 , 11 ], others have not [ 4 , 6 , 7 , 9 ]. An in vivo study by Cleveland et al [ 12 ] demonstrated that peak pressure decreases by about 30% when measured inside the body of a pig.…”
Section: Discussionmentioning
confidence: 99%
“…The increased use of computed tomography (CT) to assess urinary calculi has provided information on some stone parameters, such as mean stone density (MSD) and stone volume (SV), that could be used to predict treatment outcomes after SWL [ 1 , 2 ]. Among the various stone parameters, skin-to-stone distance (SSD) is another factor that might be able to predict the results of treatment, although its role in the prediction of treatment outcomes is still controversial [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Because the shock wave (SW) path passes through various tissues with different compositions and densities, transmission of the SW along these different tissue planes may lead to energy loss and hence affect treatment outcome [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%